Penggunaan Permainan Ular Tangga Terhadap Hasil Belajar Mata Pelajaran IPS Siswa Sekolah Dasar - Yulita Sosang Salombe (Universitas Muhammadiyah Enrekang, 2021)
This study aims to determine the use of the game of snakes and ladders on the learning outcomes of social studies subjects for elementary school students. This study uses the Meta-Analysis method with document studies from previous research results. Data collection techniques were carried out with the help of Google Scholar and Google Scholar. Based on the results of the research, the author uses 10 journals to be analyzed. From the results of the analysis of the use of snakes and ladders game media can improve student learning outcomes starting from the lowest 12.5% ​​to the highest 61.24% with an average of 31.797%.